2023
DOI: 10.1002/cam4.5889
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world data on the efficacy and safety of immune‐checkpoint inhibitors in elderly patients with non‐small cell lung cancer

Abstract: Purpose Immune‐checkpoint inhibitors (ICIs) are effective against advanced non‐small cell lung cancer (NSCLC). However, whether the efficacy and safety of ICI treatment in elderly patients are similar to those in younger patients is unclear. This study was designed to address this question. Methods We enrolled patients who received ICI monotherapy in Japan between December 2015 and December 2017; those ≥75 years of age comprised the elderly group. We compared the efficacy and safety of ICI monotherapy in elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The current lung cancer treatment strategy recommends testing for gene variants and programmed cell death ligand 1 immunohistochemistry (PD‐L1 IHC) for patients with metastatic non‐small cell lung cancer. 7 There are several reports that molecularly targeted agents and immunotherapy could be safely administered to elderly lung cancer patients, 17 , 18 , 19 emphasizing the crucial importance of making a diagnosis by FB, even for elderly patients, in order to receive appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The current lung cancer treatment strategy recommends testing for gene variants and programmed cell death ligand 1 immunohistochemistry (PD‐L1 IHC) for patients with metastatic non‐small cell lung cancer. 7 There are several reports that molecularly targeted agents and immunotherapy could be safely administered to elderly lung cancer patients, 17 , 18 , 19 emphasizing the crucial importance of making a diagnosis by FB, even for elderly patients, in order to receive appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, integrated analyses of previous clinical trials have demonstrated a significantly prolonged prognosis in elderly patients with untreated NSCLC receiving ICI therapy compared to those receiving chemotherapy alone, mirroring the outcomes seen in younger patients [ 5 ]. Moreover, real-world evidence suggests a comparable treatment efficacy between younger and older populations [ 6 , 7 , 19 ]. Our results also showed that chronological age did not affect PFS after ICI treatment, which is consistent with these results.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs) have emerged as indispensable frontline therapies to manage advanced or recurrent NSCLCs without druggable mutations [ 4 ]. However, considering the age-associated immunosenescence, confirming ICI efficacy in elderly patients is necessary, and several studies have provided valuable insights [ 5 , 6 , 7 , 8 ]. Moreover, ICIs cause a unique array of adverse effects, termed immune-related adverse events (irAEs), wherein reinvigorated immune responses may inadvertently target healthy organs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pembrolizumab monotherapy was also acceptably safe, although treatment-related AEs of grade ≥3 were more common in patients aged ≥75 years than in those aged <75 years (16.9% vs. 24.2%). In addition, several retrospective studies have demonstrated the efficacy and safety of ICI monotherapy in patients with NSCLC aged ≥75 years ( 20 , 37 - 39 ). In our prospective observational study of 31 patients with NSCLC aged ≥75 years, pembrolizumab monotherapy elicited a good therapeutic response, with a median PFS of 5.3 months, a median OS of 11.6 months, and an acceptable safety profile ( 27 ).…”
Section: Elderly Patientsmentioning
confidence: 99%